Eco-spirituality : toward a reverent life - Cummings, Charles (Mahwah, N.J. Paulist Press, 1991)
In this engaging book, Cummings builds a bridge between the seemingly poles apart topics of ecology and spirituality and explores their common concern for justice, compassion, and quality of life.
Keywords: Nature -- Religious aspects. Human ecology -- Religious aspects. Spirituality